Conscience of a conservative : a rejection of destructive politics and a return to principle - Flake, Jeff, 1962- (Random House, 2017)
Republican Senator Jeff Flake takes his party to task for embracing nationalism, populism, xenophobia, and the anomalous Trump presidency. The book is an urgent call for a return to bedrock conservative principle and a cry to once again put country before party.